Early warning systems and monitoring tools for agricultural adaptations to climate change. [Abstract only]. - Lacombe, Guillaume (2011)
In Southeast Asia, agricultural production is highly constraint by climate cycles typically characterized by the regular alternation of the wet and dry seasons, and by unpredictable droughts or rain storms. For hundreds of decades, farmers have adapted to these climate vagaries by growing various cultivars, mainly during the rainy season, with different cropping calendars, thus limiting the risk of total agricultural losses in the case of extreme events. In response to increased population and food demand, cropped land and inhabited zones are expanding to flood- and drought prone areas, resulting in higher frequency of flood and drought related damages. Climate change may magnify the severity of agricultural losses with more contrasted seasons and more extreme climate events (longest droughts and flashier floods). Communities living in flood and drought prone areas are generally the poorest and therefore the most vulnerable to natural disasters. Reducing the vulnerability of these people to the negative impacts of floods and droughts should improve their standard of living and assist them to climb out of poverty. One solution consists in forecasting and characterizing extreme climate events through the use of "early warning systems" and "monitoring tools", giving time for the population to take appropriate actions in order to minimize damages and possible casualties. The Flood Management and Mitigation Center of the Mekong River Commission is a good example of successful early warning system although some improvements, especially at the action/local levels are required. The monitoring of droughts and the prevention of their negative effects on agricultural yields is more difficult to implement as droughts are occurring at large spatial scales, affecting the society as a whole. However, recent progresses in remote sensing technologies and telecommunication systems are promising at the conditions that institutional and management supports strengthen, especially when trans-boundary coordination is required.